Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd004085.pub2
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency ventilation versus conventional ventilation for treatment of acute lung injury and acute respiratory distress syndrome

Abstract: There is not enough evidence to conclude whether high-frequency ventilation reduces mortality or long-term morbidity in patients with ALI or ARDS; further trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 17 publications
1
11
0
2
Order By: Relevance
“…28 We included six additional trials of high frequency oscillation and unpublished data provided by primary investigators, which generated additional statistical power and more precise estimates of treatment effects.…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…28 We included six additional trials of high frequency oscillation and unpublished data provided by primary investigators, which generated additional statistical power and more precise estimates of treatment effects.…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
“…[25][26][27] An earlier systematic review of randomised controlled trials found only two small trials and could not draw definitive conclusions about the effect of high frequency oscillation on mortality. 28 Additional studies have subsequently become available. Furthermore, in the context of current 29 30 and future pandemics, there is a pressing need for evidence on the effects of potentially life saving interventions for patients with ARDS.…”
Section: Introductionmentioning
confidence: 99%
“…18 Currently, no clear evidence indicates whether high frequency ventilation reduces mortality or long term morbidity in patients with acute lung injury or respiratory distress syndrome.…”
Section: Other Ventilatory Techniquesmentioning
confidence: 99%
“…There has been increasing interest in the role of high frequency oscillatory ventilation (HFOV) in adults with ARDS over the last few years, following anecdotal reports of improved oxygenation and the benefits seen in paediatrics [24]. Consideration was given to HFOV in this patient, as oscillation may potentially have made removal of the sand easier due to the mechanical effects of this mode of ventilation.…”
Section: Discussionmentioning
confidence: 99%